Pengaruh Pancasila dalam Pembaruan Hukum Pidana Indonesia untuk Memerangi Terorisme - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Karina Cahyawati; Kurnia Al Fiyatur Rohmaniyah; Choirunnisa Puspita Dewi (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to explore the influence of Pancasila in Islamic criminal law reform, focusing on efforts to combat terrorism. Using a qualitative approach, this research collects and analyzes various literature sources and relevant legal documents. In addition, document analysis was conducted to evaluate existing policies and practices, as well as challenges in the application of Pancasila principles. The results show that the integration of Pancasila can strengthen Islamic criminal law by ensuring a more just and humane application in dealing with terrorism. However, there are challenges in the reform process, including differences between sharia and Pancasila principles and implementation issues. This research recommends in-depth reforms, development of oversight mechanisms, and increased dialogue between relevant parties to create a more effective legal system that is in line with Pancasila values. The findings provide important insights for Islamic criminal law reform that is more harmonious and responsive to the threat of terrorism. The research method used is normative legal research with statutory, conceptual case, historical and comparative approaches.